Refined carbohydrates and the overfat pandemic: implications for brain health and public health policy - Maffetone, Philip; Laursen, Paul B. (Frontiers in Public Health, 2025)
Refined carbohydrate exposure—principally added sugars and rapidly digestible starches—is a modifiable driver of the overfat pandemic and carries downstream risks for brain health. This narrative review synthesizes epidemiological, clinical, and mechanistic evidence linking refined carbohydrates to excess adiposity and metabolic dysfunction, and in turn to cognitive, affective, and addiction-related outcomes. Converging data show that high-glycemic, ultra-processed foods promote positive energy balance via glycemic volatility, impaired satiety signaling, and reinforcement of dopaminergic reward pathways; chronic exposure contributes to insulin resistance, ectopic fat, systemic inflammation, and cerebrovascular burden. These states are associated with reduced executive function, attentional control, mood dysregulation, and heightened compulsive intake. Experimental studies demonstrate short-term effects on craving, reward responsivity, and glycemic variability, while longitudinal cohorts relate higher refined carbohydrate intake and markers of adiposity to poorer cognitive trajectories and greater depression risk. Although other dietary components may influence brain health, this review focuses on refined carbohydrates as a primary, tractable lever. Public health options include front-of-pack warnings for added sugars, targeted taxation and marketing restrictions (especially to children), procurement standards, reformulation targets, school and healthcare environment changes, and screening for overfat as a clinical vital sign. Priorities for research include causal trials that manipulate refined carbohydrate exposure with brain outcomes, and evaluation of policy packages at population scale. Reducing refined carbohydrate exposure offers a plausible, scalable strategy to curb overfat and protect brain health.